New position of an abdominal defensive gland complex in Staphylinidae (Coleoptera) with redescription of Piestus heterocephalus Fauvel, 1902 (Piestinae) - Caron, Edilson; Ribeiro-Costa, Cibele S.; Newton, Alfred F. (Zootaxa, 2008)
A Neotropical rove beetle, Piestus heterocephalus Fauvel, 1902 (Coleoptera, Staphylinidae, Piestinae), is redescribed and illustrated. Its abdominal defensive gland complex is described using drawings, photos and scanning electron micrographs. This complex is reported for the first time in Piestinae and its distinctive position is unique in Staphylinidae. Our preliminary survey suggests that the presence of this gland complex is restricted to part or all of the genus Piestus Gravenhorst, 1806.